The relationship between pistachio (Pistacia vera L) intake and adiposity: A systematic review and meta-analysis of randomized controlled trials. Issue 34 (21st August 2020) - Xia, Ke; Yang, Ting; An, Li-Ya; Lin, Yue-Ying; Qi, Yu-Xing; Chen, Xiong-Zhi; Sun, Da-Li
Abstract: Background: The aim of the study was to conduct a systematic review to comprehensively evaluate the relationship between pistachio intake and obesity. Methods: We searched 6 databases and acquired parameters from randomized controlled trials regarding obesity, including body weight, body mass index (BMI), and waist circumference. A fixed-effect model was applied to the meta-analysis for the weighted mean difference (WMD) between a diet with pistachios and a control diet. Results: Eleven trials including a total of 1593 subjects met the inclusion criteria. Compared to the group on a control diet, the pistachio diet group showed lower BMI values (WMD: −0.18 kg/m 2 ; 95% confidence interval [CI]: −0.26, −0.11 kg/m 2 ; I 2 = 29.8%) and no differences in body weight (WMD: −0.22 kg; 95% CI: −0.50, 0.07 kg; I 2 = 0.0%) or waist circumference (WMD: 0.76 cm; 95% CI: −0.11, 1.63 cm; I 2 = 7.0%). Conclusion: A diet with pistachios reduced BMI and had no significant effects on body weight and waist circumference. Abstract : Supplemental Digital Content is available in the text